2015
DOI: 10.1002/jcp.25206
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Notch-1 in Resistance to Regorafenib in Colon Cancer Cells

Abstract: Regorafenib, an oral small-molecule multi kinase inhibitor, is able to block Vascular Endothelial Growth Factor Receptors (VEGFR-1, 2, and 3), Platelet-Derived Growth Factor Receptors (PDGF), Fibroblast Growth Factor (FGF) receptor 1, Raf, TIE-2, and the kinases KIT, RET, and BRAF. Different studies have displayed its antitumor activity in several cancer models (both in vitro and in vivo), particularly in colorectal and gastrointestinal stromal cancers. The mechanism of resistance to regorafenib is largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
2
26
2
Order By: Relevance
“…It was demonstrated that Notch signalling is significantly upregulated in SW480 cells that are resistant to the experimentally-generated Regorafenib drug, a multi-kinase inhibitor. Interestingly, the inhibition of Notch signalling in resistant cells restored their sensitivity to Regorafenib, thus suggesting the important role of Notch in promoting resistance to chemotherapeutic drugs[ 135 ]. The dysregulation of Notch signalling in colon cancer metastasis has been studied in detail[ 136 ].…”
Section: Notch Signalling In Colorectal Cancermentioning
confidence: 99%
“…It was demonstrated that Notch signalling is significantly upregulated in SW480 cells that are resistant to the experimentally-generated Regorafenib drug, a multi-kinase inhibitor. Interestingly, the inhibition of Notch signalling in resistant cells restored their sensitivity to Regorafenib, thus suggesting the important role of Notch in promoting resistance to chemotherapeutic drugs[ 135 ]. The dysregulation of Notch signalling in colon cancer metastasis has been studied in detail[ 136 ].…”
Section: Notch Signalling In Colorectal Cancermentioning
confidence: 99%
“…Although the roles of Notch3 and S6K in cancer development have been studied, no study has been carried out to combine the expression of Notch3 and S6K in relation to the prognosis of human ovarian epithelial cancer. It is known that Notch3 and S6K may complement their common functions in cancer development, but their roles in specific tumors are unique and context-dependent [ 8 11 ]. In the present study, we first investigated the expression of Notch3 and S6K in human ovarian epithelial cancer, to verify their expression related to clinicopathological features and prognosis in human ovarian epithelial cancer and to further evaluate their potential value as biological markers of aggressiveness in ovarian cancer, with the goal of improving the management of ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NOTCH1-high expression had multivariable associations with poor outcomes in CRC (16)(17)(18)(19). NOTCH1 mediates the resistant effects of regorafenib in colorectal cancer cells (20). It has also been shown that NOTCH1 expression is a detrimental prognostic factor in patients with mCRC who receive chemotherapy plus the anti-VEGF antibody bevacizumab (21).…”
Section: Discussionmentioning
confidence: 99%